Study on Gas Control Methods Optimization for Mining Safety - Liwen He; Yingcheng Dai; Sheng Xue; Chunshan Zheng; Baiqing Han; Xin Guo (Advances in Civil Engineering)
Effective gas control is of significance for safe efficient coal mining in Haizi Coal Mine and other mines with similar geological conditions. This study concentrates on gas control theories and techniques in multiple coal seams of Haizi Coal Mine (No. 7, No. 8, No. 9, and No. 10 coal seam from top to bottom). To minimize risk of high gas emission and outburst hazard, No. 10 seam was mined first as a protective seam prior to the mining of its overlying outburst-prone No. 7, No. 8, and No. 9 seam. Four gas drainage measures were determined for gas control, including cross-measure boreholes into overlying coal seams, surface goaf wells, roof boreholes, and roof gas drainage roadway. These gas control measures, if implemented through entire coal seam extraction, would be possibly uneconomic. An investigation was undertaken to analyze effects of those four measures on gas emission, methane concentration, and gas drainage quantity in No. 2 1024 mining panel of No. 10 seam. Results indicate that the highly expensive gas drainage measure of a roof roadway has poor drainage performance and could be effectively replaced by roof boreholes. When adopting the optimized combination of gas drainage measures, drainage efficiency of No. 7 seam, No. 8 seam, and No. 9 seam could reach 58.64% and decrease gas pressure to be below 0.74 MPa. Outcomes of this study could provide beneficial guidance not only for gas drainage design optimization in Haizi Coal Mine but also for other multiple-seam mines with similar mining and geological conditions, for increasing gas drainage efficiency and guaranteeing mining safety.